Pertanggungjawaban Notaris Sebagai Pembuat Akta Wasiat (Testament Acte) Yang Tidak Memenuhi Ketentuan Legitieme Portie - Putri Shofwatul Laily (UNES Law Review, 2024)
The death of an heir has created rights for their heirs to control and/or obtain the inheritance of the deceased. According to the Western Law of Inheritance, there are two ways to inherit a portion of the deceased's estate: according to the provisions of the law and as designated in a testament. In the formation of a testament, the role of a notary is important and crucial. This is because a notary can oversee, provide advice so that the content of the heir's testament does not contradict the law. One of the rules that must not be violated in the creation of a testament is regarding the absolute rights of the heirs or legitimate portion as regulated in Article 913 of the Civil. However, in reality, there are still testaments that violate the provisions of the legitimate portion from one or all of the heirs even though the testament has been made by or before a notary. This has undoubtedly caused injustice to the heirs, and more severely, the validity of a testament is then questioned as to whether it complies with the existing laws or contravenes statutory regulations. In writing this journal, the author uses a normative juridical method, which is an approach based on primary legal materials by examining various theories, concepts, legal principles, and regulations related to this research.